2015
DOI: 10.1016/j.parint.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Cryptosporidium parvum from two different Japanese prefectures, Okinawa and Hokkaido

Abstract: Infectious diarrhea is the most frequent cause of morbidity and mortality in neonatal calves. Cryptosporidium parvum is one of the main pathogens associated with calf diarrhea. Although diarrhea is a symptom of infection with various pathogens, investigations to detect the types of pathogens have never been performed in Japan. This study investigated the prevalence of four major diarrhea-causing pathogens in calves: C. parvum, rotavirus, coronavirus, and enterotoxigenic Escherichia coli (E. coli K99). Commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…The causative agents include bacteria such as enterotoxigenic Escherichia coli (ETEC), viruses such as rotavirus, and parasites or other possible factors [10, 19]. Cryptosporidium , as an important protozoan parasite, can cause parasitic diarrhea in animals.…”
Section: Introductionmentioning
confidence: 99%
“…The causative agents include bacteria such as enterotoxigenic Escherichia coli (ETEC), viruses such as rotavirus, and parasites or other possible factors [10, 19]. Cryptosporidium , as an important protozoan parasite, can cause parasitic diarrhea in animals.…”
Section: Introductionmentioning
confidence: 99%
“…Infections of Cryptosporidium parvum , C. bovis , C. ryanae and C. andersoni have been reported in cattle [ 5 , 8 , 9 , 13 ]. The zoonotic subtype C. parvum [ 13 ] causes severe watery diarrhea in calves [ 3 ]. Although C. parvum has traditionally been diagnosed by the size and morphology of oocysts detected in fecal samples, the oocysts of C. parvum cannot be discriminated from those of C. bovis and C. ryanae , which are most likely asymptomatic [ 10 ].…”
mentioning
confidence: 99%
“…IIa, IId and IIl subtype families have been detected in calves worldwide, with the zoonotic subtype IIaA15G2R1 of the IIa subtype family most frequently reported [ 13 ]. Previous studies on C. parvum GP60 sequences from Hokkaido [ 5 ], Gifu [ 1 ], Hyogo [ 9 ] and Okinawa [ 3 ] Prefectures, Japan, indicated that IIaA15G2R1 was the only subtype distributed in these regions. However, the number of samples and locations analyzed in those studies were insufficient to determine the genetic variation of C .…”
mentioning
confidence: 99%
“…Among those factors, bovine rotavirus (BRV) infection and bovine cryptosporidiosis are prevalent among cattle in Japan, and cause severe diarrhea in calf [1]. Bovine rotavirus infects cattle of all ages, but calf has a higher incidence and more severe symptoms [2]. Bovine cryptosporidiosis with diarrhea caused by Cryptosporidium parvum results in decreased appetite, weakness, and dehydration in calf [3].…”
Section: Introductionmentioning
confidence: 99%